Translanguaging as interactional resources employed by students in EFL student-led group task interaction - Yang, Hao; Foley, Joseph (Journal of English Language and Linguistics, 2024)
This study aimed to investigate the strategies used by students during group task interaction in an EFL classroom. It also focused on translanguaging practices as one of the interactional resources to facilitate communication and interaction among students. The data were collected by recording the classroom discussions of a focused group in an EFL class at a Chinese university over three class hours. The analysis was carried out using conversation analytic methodology. The study revealed various interactional features in turn construction. Students often used single learner turns to show their agreement and extended learner turns with clarification or explanation to support their ideas for turn-taking. Concerning turn passing, students prefer to use open-ended questions to ask for opinions; they also use open-ended questions to ask for opinions, confirmation checks for meaningful understanding, and extended wait times for other speakers to take turns. Moreover, gaze was also noticed when they passed the turn to the others. Regarding self-repairs and peer repairs, they often made content-focused repairs rather than form-focused ones, and students with higher English proficiency usually provided support. Translanguaging was an effective strategy to facilitate peer interaction and avoid errors in meaning-making. This study has important implications for language teaching and learning policy, highlighting the need to encourage prospective teachers to practice translanguaging to facilitate classroom interaction and second language acquisition.